2007
DOI: 10.1080/13545700701439432
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and gendered wages in urban China

Abstract: This paper documents the changing impact of foreign direct investment (FDI) on gendered wages in urban China. Combining household survey data from 1995 and 2002 with province-level macro-data, the paper finds that FDI as a proportion of investment has a sizable and statistically significant positive effect on both female and male wages in both years. In 1995, women experienced larger gains from FDI than men, but those gender-based advantages had reversed by 2002, with men experiencing larger wage gains from FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…Foreign direct investment (FDI) in China has, in the long run, appeared to have provided greater "wage gains" to men than to women (Braunstein and Brenner, 2007). Shu et al (2007) found gender differentials in FDI employment, with women concentrated in lower-paid "export-oriented manufacturing industries" rather than "high-paying foreign firms and joint ventures".…”
Section: The Position Of Women In Employment In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign direct investment (FDI) in China has, in the long run, appeared to have provided greater "wage gains" to men than to women (Braunstein and Brenner, 2007). Shu et al (2007) found gender differentials in FDI employment, with women concentrated in lower-paid "export-oriented manufacturing industries" rather than "high-paying foreign firms and joint ventures".…”
Section: The Position Of Women In Employment In Chinamentioning
confidence: 99%
“…However, although almost as many women as men work in China, for some this is by necessity due to low wages. Furthermore, there is low representation in more senior roles often due to opaque promotional procedures (Cooke, 2001(Cooke, , 2004(Cooke, , 2005(Cooke, , 2008bCatalyst, 2008), compounded by poor job mobility prospects (Cao and Hu, 2007), occupational segregation (Cai and Wu, 2006), work and pay inequalities particularly for married women with children and for those working in externally owned, FDI-funded plants (Braunstein and Brenner, 2007;Shu et al, 2007), and in particular for women migrant workers (Feng and Anan, 2003;Liang and Chen, 2003;Ngai, 2004;Tam, 2008). The "bamboo curtain" (Tan, 2008) and the economic opportunities now open to many women (Cooke, 2005) have influenced the creation of many new ventures that are women-led.…”
Section: The Position Of Women In Employment In Chinamentioning
confidence: 99%
“…Both women and men may benefit from increased economic opportunities, but because women are universally paid less than men and their labor is more contingent they typically gain less than do their male counterparts. A recent analysis of women and men working in foreign export manufacturing zones in China, for example, found that women received smaller wage gains compared to men (Braunstein and Brenner 2007). Secondly, pre-existing gender inequality is often used intentionally to attract foreign investment and economic growth and, in some cases, might be a prerequisite for it (Seguino 2000).…”
Section: Box 247: Norms Of Femininity and Masculinity In Cosmetics mentioning
confidence: 99%
“…They acknowledge that their independent variables are at different levels of aggregation, which causes a downward bias when estimating regression coefficient standard errors. The issue has been addressed by estimating standard errors clustered on provinces (Braunstein and Brenner 2007). However, like Braunstein and Epstein (2002), this model does not contain price expectation as one of the independent variables as well, which is a weakness of this model.…”
Section: Review Of Macroeconomic Wage Modelsmentioning
confidence: 99%
“…Braunstein and Brenner (2007) combine macroeconomic-level data and microeconomiclevel data, which is the key innovation of their study. They acknowledge that their independent variables are at different levels of aggregation, which causes a downward bias when estimating regression coefficient standard errors.…”
Section: Review Of Macroeconomic Wage Modelsmentioning
confidence: 99%